A homozygous truncating ETV4 variant in a Nigerian family with congenital anomalies of the kidney and urinary tract. Issue 5 (24th January 2023) - Kolvenbach, Caroline M.; Zheng, Bixia; Merz, Lea M.; Mertens, Nils D.; Mansour, Bshara; Wang, Chunyan; Seltzsam, Steve; Schneider, Sophia; Schierbaum, Luca; Pantel, Dalia; Chen, Jing; van der Ven, Amelie T.; et al.
Abstract: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most prevalent cause of chronic kidney disease that manifests in children. To date ~23 different monogenic causes have been implicated in isolated forms of human CAKUT, but the vast majority remains elusive. In a previous study, we identified a homozygous missense variant in E26 transformation‐specific (ETS) Variant Transcription Factor 4 ( ETV4 ) causing CAKUT via dysregulation of the transcriptional function of ETV4, and a resulting abrogation of GDNF/RET/ETV4 signaling pathway. This CAKUT family remains the only family with an ETV4 variant reported so far. Here, we describe one additional CAKUT family with a homozygous truncating variant in ETV4 (p.(Lys6*)) that was identified by exome sequencing. The variant was found in an individual with isolated CAKUT displaying posterior urethral valves and renal dysplasia. The newly identified stop variant conceptually truncates the ETS_PEA3_N and ETS domains that regulate DNA‐binding transcription factor activity. The variant has never been reported homozygously in the gnomAD database. To our knowledge, we here report the first CAKUT family with a truncating variant in ETV4, potentially causing the isolated CAKUT phenotype observed in the affected individual.